Finite-time fluctuation theorem for diffusion-influenced surface reactions. (22nd August 2018) - Gaspard, Pierre; Kapral, Raymond
Abstract: A finite-time fluctuation theorem is proved for the diffusion-influenced surface reaction in a domain with any geometry where the species A and B undergo diffusive transport between the reservoir and the catalytic surface. A corresponding finite-time thermodynamic force or affinity is associated with the symmetry of the fluctuation theorem. The time dependence of the affinity and the reaction rates characterizing the stochastic process can be expressed analytically in terms of the solution of deterministic diffusion equations with specific boundary conditions.